Comparative study on mechanoluminescence of Eu2+ doped phosphate based phosphors. - Sahu, A K; Chowdhary, P S; Nayar, V; Dhoble, S J; Dubey, K K (Recent Research in Science and Technology, 2012)
Eu2+ doped phosphate based phosphors were prepared by solid state diffusion technique. The phosphors have simple glow curve with single peak It is clear that the ML intensity increases with increasing concentration of Eu, attained an optimum value for 1 mole % for Sr5(PO4)3Cl:Eu2+, and 2 mole% for Li3PO4:Eu2+ and LaPO4:Eu2+, then decreases with further increase in concentration of Eu. The trapping and detrapping of charge carriers in the material can be studied using ML. It is believed that in the dynamic process of loading, internal friction originating from defects activates holes released from traps and stimulates mechanoluminescience. This phosphor can be used in the dosimetry of ionizing radiations using mechanoluminescence.